Three‐dimensional Martian ionosphere model: II. Effect of transport processes due to pressure gradients. Issue 7 (21st July 2014) - Chaufray, J.‐Y.; Gonzalez‐Galindo, F; Forget, F.; Lopez‐Valverde, M.; Leblanc, F.; Modolo, R.; Hess, S.; Yagi, M.; Blelly, P.‐L.; Witasse, O.
Abstract To study the transport of the ionospheric plasma on Mars, we have included a 3‐D multifluid dynamical core in a Martian general circulation model. Vertical transport modifies the ion density above ~160 km on the dayside, especially the ions produced at high altitudes like O+, N+, and C+. Near the exobase, the dayside to nightside flow velocity reaches few hundreds of m/s, due to a large horizontal pressure gradient. Comparison with Mars Express/Analyzer of Space Plasmas and Energetic Atoms‐3 measurements between 290 and 500 km suggests that this flow could account for at least 20% of the flow produced by the solar wind. This flow is not sufficient to populate substantially the nightside ionosphere at high altitudes, in agreement with recent observations, because of a strong nightside downward flow produced by vertical pressure gradient. The O2+ and NO+ ion densities on the nightside at low altitudes (~130 km) are modified by this downward flow, compared to simulated densities without ion dynamics, while other ions are lost by chemical reactions. Variability at different time scales (diurnal, seasonal, and solar cycles) are studied. We simulate diurnal and seasonal variations of the ionospheric composition due to the variability of the neutral atmosphere and solar flux at the top of the atmosphere. The ionospheric dynamics are not strongly affected by seasons and solar cycles, and the retroaction of the ionosphere on the neutral atmosphere temperature and velocity is negligible compared to other physical processes below the exobase.